Fragility Fracture Risk in Elderly Patients With Cervical Myelopathy. Issue 2 (15th January 2019) - Horowitz, Jason A.; Puvanesarajah, Varun; Jain, Amit; Raad, Micheal; Gjolaj, Joseph P.; Shen, Francis H.; Hassanzadeh, Hamid
Abstract : Study Design: Retrospective review. Objective: To identify and compare the incidences of fragility fractures amongst three elderly populations: the general population, patients with surgically treated cervical spondylotic myelopathy (CSM), and patients with CSM not surgically treated. Summary of Background Data: CSM is a common disease in the elderly. Progression of myelopathic symptoms, including gait imbalance, can be a source of morbidity as it can lead to increased falls. Methods: Records of elderly patients with Medicare insurance from 2005 to 2014 were retrospectively reviewed. Three mutually exclusive populations of patients were identified for analysis, including a cohort of patients with a diagnosis of CSM who were not treated with surgery; a cohort of patients with CSM who were treated with surgery; and a group of control patients who had never been treated with cervical spine surgery nor were diagnosed with CSM. Incidence of fractures of the distal radius, proximal humerus, proximal femur, and lumbar spine were assessed and compared between cohorts, adjusted by age, sex, osteoporosis, dementia, cerebrovascular disease, and Charlson Comorbidity Index. Results: A total of 891, 864 patients were identified, of which 60, 332 had a diagnosis of CSM and 24, 439 underwent cervical spine surgery. Compared to general population controls, the 12-month adjusted odds of experiencing at least one fragility fracture were 1.59 times higher in patients with CSM who were not treated with surgery ( P  < 0.001). The analogous odds ratio was 1.34 ( P  < 0.001) at 3 years. Compared to nonsurgically treated patients with CSM, the odds of experiencing at least one fragility fracture were reduced to 0.89 in surgically treated patients ( P  = 0.008). Conclusion: Fragility fractures are a significant source of morbidity and mortality in elderly patients. CSM is associated with increased rates of fragility fractures, although surgical management of CSM may be protective against risk of fragility fracture. Level of Evidence: 3 Abstract : In this retrospective database review of 891, 864 elderly Medicare patients, patients with cervical spondylotic myelopathy experienced increased odds of sustaining a fragility fracture compared to the general population, and the myelopathy patients treated with surgical decompression experienced decreased odds of sustaining a fragility fracture compared to those not surgically treated.